Development of social statistical databases and a methodological approach for the development of a social vulnerability index for small island developing states (2001)
Notes that the objective of the project is to improve the social conditions of persons living in ECLAC/CDCC member countries by strengthening the capacity of policy makers to formulate, implement and evaluate social policies.
Keywords: SOCIAL STATISTICS